Efecto de la aplicación de dos bioestimulantes comerciales en el crecimiento de las plantas de cacao clon nacional (theobroma cacao l) en la Zona de Buena Fe - Arguello Cedeño, Edison Fredy (2015)
The work was carried out in the property Rose, sector May twenty four, belonging to the Canton Good Faith, County of The Ríos. The objectives were to Evaluate the effect of the application of two commercial bioestimulantes in the growth of the plants of cocoa national clone (Theobroma cocoa L) in the area in good faith, to evaluate three application dose with the bioestimulantes Ryzup and Cytokin in nursery stage in plants of cocoa national clone (Theobroma cocoa L), to evaluate the combination of Cytokin and Ryzup in the plants of cocoa to determine difference that it exists in this combination and to Determine which of the treatments in study generates the biggest plant height to the ninety days. The design experimental employee totally at random (DCA). to determine the differences among the treatments he/she was carried out the test from Tukey to 0.5% of probability. Ten treatments T1 was used Without Bioestimulante, T2 Ryzup Low Dose (10 gr), T3 Ryzup Half Dose (20 gr), T4 Ryzup High Dose (30 gr), T5 Cytokin Low Dose (100 cc), T6 Cytokin Half Dose (200 cc), T7 Cytokin High Dose (300 cc), T8 Ryzup + Cytokin Low Dose (10 gr + 100 cc), T9 Ryzup +Cytokin Half Dose (20 gr + 200 cc), and T10 Ryzup +Cytokin High Dose (30 gr + 300 cc) and four repetitions. The evaluated variables went plant height at the 45, 60, 75 and 90 days. Obtaining maximum values of 28.40, 35.66, 43.17, 44.88 centimeters respectively and values minima of 16.34, 18.61, 19.85, 25.12. plant Diameter at the 45, 60, 75 and 90 days getting maximum values of 1.59, 1.94, 2.14, 2.40 centimeters respectively and values minima of 1.47, 1.81, 2.04, 2.31 centimeters. For the variable numbers of leaves, long of root, root weight was achieved maximum values of 16.45 units, 40.88 centimeters and 8.75 grams it is necessary to indicate that these it corresponds to the 90 days that I last the work